Subiektywność a historyczność: myśląc o krytyce fenomenologii w hermeneutyce - Geniusas, Saulius (Wydawnictwo Naukowe UAM, 2011)
The paper is meant to accomplish a twofold goal. First, it aims to spell out some implications that are entailed, although not fully spelled out, in my Husserl’s Notion of the Primal Ego in Light of the Hermeneutical Critique. Secondly, this paper also aims to answer Witold Płotka’s multifaceted critique of my Husserl’s Notion… that he articulated in his Does the Primal Ego have a Historical Character? With this twofold goal in mind, I argue that (1) Husserl’s notion of transcendental subjectivity is historical through and through and that (2) the historical nature of transcendental subjectivity compels one to rethink the hermeneutical critique of phenomenology. I further suggest that the freeing of Husserl’s notion of the primal ego from the hermeneutical critique opens a new space to pursue a dialogue between phenomenology and hermeneutics. Such a dialogue should lead to the realization that the problematic of the primal ego can in significant ways enrich the hermeneutical accounts of self-understanding.
Keywords: Fenomenologia; Phenomenology; Hermeneutyka; Hermeneutics; Subiektywność; Subjectivity; Pierwotne ego; Primal ego; Historyczność; Historicity